2010
DOI: 10.1259/bjr/13711326
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of CT parameters for assessment of tumour size and aggressiveness in lung adenocarcinoma with bronchoalveolar elements

Abstract: Accurate determination of tumour size in lung adenocarcinoma with bronchoalveolar features (BAC) is important for the determination of TNM (tumour, nodes, metastasis) scores used in staging, prognosis and therapy response assessment. However, tumour sizes derived using lung window (LW) CT or soft-tissue/mediastinal window (MW) CT often give different results. This study examines which measurement correlates best with actual tumour size and which best identifies advanced disease. This retrospective study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Several other papers report on attempts for objective methods other than the calculation of GGO ratio and TDR to evaluate the quantitative aspects and characterization of an SSN [19][20][21][22][23][24]. Some use a one-dimensional analysis [22,24] by measuring the diameter or a combination of diameter and density of the components of an SSN on a one-dimensional histogram of the nodule.…”
Section: Discussionmentioning
confidence: 99%
“…Several other papers report on attempts for objective methods other than the calculation of GGO ratio and TDR to evaluate the quantitative aspects and characterization of an SSN [19][20][21][22][23][24]. Some use a one-dimensional analysis [22,24] by measuring the diameter or a combination of diameter and density of the components of an SSN on a one-dimensional histogram of the nodule.…”
Section: Discussionmentioning
confidence: 99%
“…components represent the lepidic growth and that solid components are frequently related with invasion [11][12][13][14][15][16][17][18][19][20][21][22][23] and also note that computed tomography (CT) plays an important role in the management of subsolid nodules. 10 It has also been suggested that the T staging in the Tumor Node Metastasis classification should be adjusted radiologically by measuring the solid component of subsolid nodules 1 and that the management of subsolid nodules should be based on the size of subsolid nodules and the solid component.…”
mentioning
confidence: 99%
“…Furthermore, it may be possible to improve TNM staging for lung adenocarcinomas that have a lepidic component by using the invasive size to predict tumour size rather than total size both by pathologic and CT assessment. There is already data in the pathology and CT literature that suggests this may be true [27][28][29][30]. If this turns out to be validated in future studies, in the next edition of the TNM it may be possible to use new terms for AIS and MIA, so Tis (adenocarcinoma) can be used for AIS and Tmi (adenocarcinoma) for MIA.…”
Section: Classification In Resection Specimensmentioning
confidence: 88%